Spherical core-shell Al@Al2O3 filled epoxy resin composites as high-performance thermal interface materials. (August 2019) - Mao, Dasha; Chen, Jiahui; Ren, Linlin; Zhang, Kai; Yuen, Matthew M.F.; Zeng, Xiaoliang; Sun, Rong; Xu, Jian-Bin; Wong, Ching-Ping
Abstract: With the miniaturization, high power density, and high integration of modern electronics, heat accumulation has emerged as a critical issue that affects their performance and reliability. The application of thermal interface materials is a common thermal management strategy. Herein, we report thermally conductive and insulating thermal interface materials composed of core-shell structured Al@Al2 O3 and epoxy resin. The composites exhibit thermal conductivity of 0.92 W m −1  K −1 at 60 wt% filler contents, which is about 4.2 times higher than that of the epoxy resin. The oxidation of Al particles results in the formation of dense nanoscale insulating Al2 O3 shell, which effectively restricts the electron transfer, thus leading to a very high electrical resistivity and puncture voltage of the composites. The polymer composites filled with Al@Al2 O3 particles have excellent insulation property, high thermal conductivity and outstanding thermos-mechanical performance, which could be a potential thermal interface material in advanced electronic packaging techniques.